2001
DOI: 10.1264/jsme2.2001.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land-Use Change in Tropical Peat Soil on the Microbial Population and Emission of Greenhouse Gases

Abstract: Effects of land-use change in tropical peatlands on the microbial population and emissions of nitrous oxide (N 2 O), methane (CH 4 ) and carbon dioxide (CO 2 ) were studied in the field and laboratory. The study area covered secondary forest, paddy field and paddy-soybean rotation field in Indonesia.ATP content, and numbers of viable bacteria and fungi, cellulolytic bacteria and fungi, NH 4 + oxidizers and denitrifiers in a paddy-soybean rotation field and paddy field were reduced to 1-30% and 3-90% of those i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
2
28
0
1
Order By: Relevance
“…On the other hand, mixed crop plantations consisting of up to only five plant species, supported the most diverse bacterial communities. Agree with Hadi et al (2001) that land conversion from secondary forest to paddy fields (monoculture plantations) led to a decrease in carbon content, together with a decrease in microbial abundance, which is consistent with this findings. Low bacterial diversity in OPP, as seen in this study, can be sensitive to environmental pressures.…”
Section: Resultssupporting
confidence: 85%
“…On the other hand, mixed crop plantations consisting of up to only five plant species, supported the most diverse bacterial communities. Agree with Hadi et al (2001) that land conversion from secondary forest to paddy fields (monoculture plantations) led to a decrease in carbon content, together with a decrease in microbial abundance, which is consistent with this findings. Low bacterial diversity in OPP, as seen in this study, can be sensitive to environmental pressures.…”
Section: Resultssupporting
confidence: 85%
“…Based on a field study conducted in Jambi, Indonesia, Furukawa et al (2005) reported that CO 2 emissions from tropical peatlands under different land-use management (coconut (Cocos nucifera) field, pineapple (Ananas comosus) field and swamp forest) ranged from approximately around 0.72 to 6.38 g C m −2 day −1 . In addition, field studies conducted in secondary forest and paddy field in tropical peatlands, South Kalimantan, resulted in CO 2 emissions of approximately around 3.36-6.62 g C m −2 day −1 (Hadi et al, 2001). The higher CO 2 emissions recorded in field studies compared with the soil columns likely occur because peat soils in the field have different substrates and microbial populations, which develop in response to long-term differences in water table position and soil managements (Moore and Dalva 1993).…”
Section: Carbon Dioxide Emissionsmentioning
confidence: 99%
“…Peatlands cover approximately 3.3% of the land surface area (Hadi et al 2001). Tropical peatlands have been estimated to store up to 15-19% of the global peat carbon (C) pool (Page et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peatland deforestation, degradation and fires are estimated to have increased carbon dioxide emissions by 0.5 Pg C year −1 [4] [5]. In addition, studies on the impact of agriculture confirm that methane emissions from paddy cultivations are significantly higher (33%) than those from secondary forest [6]. Martikainen, Nykänen [7] found that the rates of mineralization of organic matter and soil microbial nitrous oxide production had also increased in the drier northern peatlands of Finland.…”
Section: Introductionmentioning
confidence: 99%